PENGEMBANGAN MODEL PEMBELAJARAN BLENDED LEARNING BERBASIS EXPERIENTAL PADA MATA KULIAH DASAR- DASAR GEOGRAFI PROGRAM STUDI DIII TEKNOLOGI PENGINDERAAN JAUH UNIVERSITAS NEGERI PADANG - Dewi Ramadhan (Jurnal Pendidikan, 2021)
Higher education as higher education in Indonesia is demanded to be able to anticipate the rapid development of technology that occurred in the era of the industrial revolution 4.0 The research objective is to implement an experiential-based Blended learning model developed in the Geography Basics course. In geography, the application of science and technology such as computers and internet networks is very important in studying geospatial phenomena that occur on the surface of the earth. The results of the development of learning innovations that have been carried out, ranging from conceptual, product innovations obtained, supporting technology used, and its implementation in the learning process can be said to make it easier for students to understand the subject of geography. Geography is the study of space, by looking for literature about the phenomena that occur can provide an understanding of students' spatial thinking. With innovative and creative learning videos, during the learning process students are motivated and enthusiastic about the video presentation at the time of presentation by each group so that the discussion forum is not rigid and makes students more active in asking, answering, responding or criticizing in the learning process in the classroom